Aima (1974)
Keywords: 1.Conservation 保護; Good

Aima (1974)
Keywords: 1.Conservation 保護; Good

Celebração Litúrgica Ciclo C 1973-1974 (edições Theologica, 1974)
Keywords: 10.Cover Damage; Good

Directory on Children's Masses with an Appendix on The Eucharistic Prayers (Catholic Truth Society, 1974)
Keywords: 1.Conservation 保護; Good

Já Sei Ler Livro de Leitura Da 2a Classe (Ensino Primario) (Edições, 1974)
2 copies

Leccionário Ano A (União Gráfica, 1974)
Keywords: Good

Missal Bíblico Diário (Difusora Bíblica, 1974)
Keywords: Good

Missal Bíblico Festivo (Missionários Capuchinhos, 1974)
Keywords: Good

Missal dominical (Edições Paulinas, 1974)
Keywords: Good

Missal Romano, Leccionario Ano A (Uniao Grafica, 1974)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

O Novo "Ordo Paenitentiae" interpela o Sacerdote (Composto e Impresso, 1974)
Keywords: 1.Conservation 保護; Good

Pastoral dos Sacramentos, Subsidios Liturgico-Catequeticos (Edicoes Paulinas, 1974)
Keywords: 1.Conservation 保護; Good

通用漢英辭典 = General Chinese-English dictionary (中華書局(香港)有限公司, 1974)
OCLC: 43610383
Keywords: Chinese language; Dictionaries; DictionariesDictionariesChinese language Dictionaries English; DictionariesDictionariesChinese language Dictionaries French; DictionariesDictionariesDictionaries; DictionariesDictionariesDutch language Dictionaries English; DictionariesDictionariesEncyclopedias and dictionaries; DictionariesDictionariesEncyclopedias and dictionaries Specimens; DictionariesDictionariesEnglish language 20th century Dictionaries; DictionariesDictionariesEnglish language 20th century Dictionaries Chinese; DictionariesDictionariesEnglish language Australia Dictionaries; DictionariesDictionariesEnglish language Dictionaries; DictionariesDictionariesEnglish language Dictionaries Chinese; DictionariesDictionariesEnglish language Dictionaries Dutch; DictionariesDictionariesEnglish language Dictionaries French; DictionariesDictionariesEnglish language Dictionaries Latin; DictionariesDictionariesEnglish language Dictionaries Portuguese; DictionariesDictionariesEnglish language Dictionaries Spanish; DictionariesDictionariesEnglish language Idioms - Dictionaries; DictionariesDictionariesEnglish language Idioms Dictionaries; DictionariesDictionariesEnglish language New words Dictionaries; DictionariesDictionariesEnglish language Orthography and spelling Dictionaries; DictionariesDictionariesEnglish language Pronunciation Dictionaries; DictionariesDictionariesEnglish language–Dictionaries–Spanish; DictionariesDictionariesFrench language Dictionaries Chinese; DictionariesDictionariesFrench language Dictionaries English; DictionariesDictionariesFrench language French-English; English-French dictionaries; DictionariesDictionariesItalian language Dictionaries; DictionariesDictionariesLatin language Dictionaries English; DictionariesDictionariesLatin language Dictionaries French; DictionariesDictionariesMultilingual dictionaries; DictionariesDictionariesPortuguese language - Portuguese & English dictionaries; DictionariesDictionariesPortuguese language Dictionaries Chinese; DictionariesDictionariesPortuguese language Dictionaries English; DictionariesDictionariesSpanish language Dictionaries English; DictionariesDictionariesSpanish language–Dictionaries–English; DictionariesDictionariesdictionaries; DictionariesDictionariespolyglot dictionaries; Dictionnaires multilingues

Question and answer: graded oral comprehension exercises - Alexander, L. G. (Longmans, 1974)
2 copies
Keywords: Anglais (Langue) Anglais parlé; Anglais (Langue) Manuels pour allophones; English language; English language Spoken English; English language Textbooks for foreign speakers; Textbooks for foreign speakers

A New Syllabus English 3 for Hong Kong Secordary Schools - Alter, J. B. (Language Research Services Ltd, 1974)

New Syllabus English for Hong Kong Secondary Schools 1 - Alter, J. B. (Language Research Services Ltd, 1974)

New Syllabus English for Hong Kong Secondary Schools 2 - Alter, J. B. (Language Research Services Ltd, 1974)

Moral E Evangelizacao Hoje - Bernhard Haering (Edicoes Paulinas, 1974)
Stamp of unknown
Keywords: Good

Curso- Convivencia de Espiritualidade Sacerdotal - Bifet, Joao Esquerda (Uniao Apostolica Do Clero, 1974)
Keywords: 1.Conservation 保護; Good

Music appreciation for Australian schools - Cameron, Alexandra E. (Cheshire, 1974)
OCLC: 220304964
Keywords: Analyse musicale; Musical analysis

漢語成語詞辭 - Commercial Press (Commercial Press, 1974)

Literatura prática 2 ano Curso Complementar - Dos Santos Carriço, Lilaz (Porto, 1974)

English 900 A Basic Course Three - English Language Services (Macmillan, 1974)

Mastering modern English: a certificate course - Etherton, A. R. B. (Longman, 1974)
OCLC: 216896548
Keywords: Anglais (Langue) Composition et exercices; Anglais (Langue) Étude et enseignement; English language Composition and exercises; English language Grammar; English language Study and teaching

My book of English exercises = gramática exemplificada da lingua ïnglesa exercicios de conversação - Franco, Ferraz (Porto Editora, 1974)
OCLC: 8241231
Keywords: Portuguese language; Portuguese language Textbooks for foreign speakers Portuguese; Textbooks for Portuguese speakers

Novo dicionário de termos técnicos inglês-português vol. 1 - Fürstenau, Eugênio (Editora Globo, 1974)
OCLC: 1245630222
Keywords: Dictionaries; English language; English language Dictionaries Portuguese; Technologie Dictionnaires anglais; Technology; Technology Dictionaries; technical dictionaries

Aids to Oral English for Hong Kong Senior Course - Grant, T. A. (Universial Publications Ltd, 1974)

Aids to English Conversation Senior Series Book 1 - Grant, T. A.; Dewar, B. (Universial Publications Ltd, 1974)

Medicina e Moral no Seculo XX - Haring, Bernhard (Editoral Verbo, 1974)
Signature
Keywords: 1.Conservation 保護; Good

Choosing your English - Haycraft, John; Creed, T. S. (BBC English by Radio & Television, 1974)
OCLC: 221137503
Keywords: Anglais (Langue) Enregistrements sonores pour allophones; Anglais (Langue) Manuels pour allophones; English language; English language Sound recordings for foreign speakers; English language Study and teaching Foreign speakers Audio-visual aids; English language Textbooks for foreign speakers; Sound recordings for foreign speakers; Textbooks for foreign speakers

Active English - Teachers' Notes to Book Five - For Hong Kong Primary Schools - Howe, D. H. (Oxford University Press, 1974)
Keywords: Anglais (Langue); English language

Active English - Teachers' Notes to Book Four - For Hong Kong Primary Schools - Howe, D. H. (Oxford University Press, 1974)
Keywords: Anglais (Langue); English language

Active English - Teachers' Notes to Book One - For Hong Kong Primary Schools - Howe, D. H. (Oxford University Press, 1974)
Keywords: Anglais (Langue); English language

Active English - Teachers' Notes to Book Two - For Hong Kong Primary Schools - Howe, D. H. (Oxford University Press, 1974)
Keywords: Anglais (Langue); English language

Active English - Teachers' Notes to Introductory Book - For Hong Kong Primary Schools - Howe, D. H. (Oxford University Press, 1974)
OCLC: 298368832
Keywords: Anglais (Langue); English language

Objeccoes Religiosas dos Jovens - Lariviere, Jean- Jacques (Edicoes Paulinas, 1974)
Signature
Keywords: 1.Conservation 保護; Good

A Historia e os Homens da Primeira Republica Democratica do Oriente - Lessa, Almerindo (Imprensa Nacional, 1974)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Meditacoes - Lubich, Chiara (Imprimatur, Conego Carlos Pinheiro, 1974)
Keywords: 1.Conservation 保護; Good

Sim, Sim. Nao, Nao - Lubich, Chiara (Edicao do Movimento dos Focolares, 1974)
Keywords: 1.Conservation 保護; Good

Textos de Psicología - Luiza Guerra, Maria (Porto Editora, 1974)
2 copies

Beyond Conventional Christianity - Mateos, Juan (East Asian Pastoral Institute, 1974)
Keywords: 1.Conservation 保護; Good

The Modern School Visual Geographies. Book 6: The U.S.S.R., the Near and Far East - May, Stella (Evans Bros, 1974)
OCLC: 270890971
Keywords: Eastern Asia Description and travel Juvenile literature; Juvenile works; Middle East; Middle East Description and travel Juvenile literature; Soviet Union; Soviet Union Description and travel Juvenile literature; Travel; URSS Descriptions et voyages Ouvrages pour la jeunesse

20th Century Folk Hymnal - Mayhew, Kevin (Mayhew-McCrimmon, 1974)
OCLC: 7578741
Keywords: Hymns; English

Reading English - Meacham, William (Chiu Ming Publishing, 1974)

Read it, write it. 2 - Methold, Ken (Longman (Far East), 1974)
OCLC: 314640597

Read it, write it. 3 - Methold, Ken (Longman (Far East), 1974)
OCLC: 314640597

Talking in English 2: teacher's book - Methold, Ken (Longman, 1974)
OCLC: 957032421
Keywords: Anglais (Langue) Anglais parlé; Conversation and phrase books; English language; English language Conversation and phrase books Japanese; English language Spoken English; English language Spoken English Study and teaching Japanese speakers

Apologia Pro Vita Sua - Newman, Cardeal (Editorial Verbo, 1974)
Stamp
Keywords: 1.Conservation 保護; Good

A Guided picture composition for Hong Kong 1 - Norton, Brenda A. (Highway Educational Press, 1974)
2 copies
Keywords: Anglais (Langue) Composition et exercices; English language; English language Composition and exercises; English language Textbooks for foreign speakers Chinese; Textbooks for Chinese speakers

The Malacca Thaumaturge Wonder - Worker II, 1545-1552 - Pintado, M. J. (The Voice of The Ruins, 1974)
Keywords: 1.Conservation 保護; Good

A Nova Criacao - Rey, Bernard (Impresso na Grafica de Edicoes Paulinas, 1974)
Keywords: 1.Conservation 保護; Good

Compêndio de Biologia 2.º Ano do Curso Complementar - Roque, Mercês; Castro, Adalmiro (Porto Editora, 1974)

Método de Harmônio (Primeiro e Segundo Curso) - Sousa Maroues, José (Editorial Franciscana, 1974)
3 copies

Befreit aus Enge un zwang - Steinmetz, Franz-Josef (Verlag Katholisches Bibelwerk GmbH Stuttgart, 1974)
Keywords: 1.Conservation 保護; Good

More modern short stories: for students of English - Taylor, Peter J. W. (Oxford University, 1974)
Ten unabridged short stories by twentieth-century authors of various nationalities, including Hemingway, Joyce, Naipaul, Dahl, Greene, and Lessing.
OCLC: 16555530
Keywords: Anglais (Langue) Manuels pour allophones; English language; English language - Readers - For non-English speaking students; English language Textbooks for foreign speakers; Readers; Readers 1950-; Since 1950; Textbooks for foreign speakers

Enjoy Learning English Book I - Vilela, Margarida; Torre, Manuel; Fontes, Serafim (Didática, 1974)
2 copies

漢英科技常用詞匯 - 中國科學院翻譯室 (商務印書館香港分館, 1974)
OCLC: 23038316
Keywords: Chinese language; Chinese language Dictionaries English; Dictionaries; Dictionnaires; Dictionnaires multilingues; Multilingual dictionaries; Science; Science Dictionaries Chinese; Technology; Technology Dictionaries Chinese; dictionaries; polyglot dictionaries

高級中學 地理 (第二冊) - 國立編譯館; 孫, 宕越 (國立編譯館, 1974)

按着拍子唱 - 安, 其那 (聞道出版社, 1974)

愛的科學: 里修小德蘭言行的硏究 = The Science of Love : A Study in the Teachings of Thérèse of Lisieux - 宋超羣; 吳經熊 (光啓出版社, 1974)
OCLC: 47796610
Keywords: Dieu (Christianisme) Adoration et amour; God (Christianity) Worship and love; Thérèse; de Lisieux; Saint; 1873-1897

英語單字記憶術 - 岩田, 一男 (文琪山版社, 1974)
OCLC: 1338508421
Keywords: 英國語言

古曲新譯: 林樂培作品12 - 林, 樂培 (d'lam productions, 1974)

Successful Way to Totel=托福測驗資料 - 海外留英托福服務中心, 編輯部 (海外留英托福服務中心, 1974)
Printed in Macau

國史多項選擇題作業 - 海天出版社編輯組 (海天出版社, 1974)

知音集 = Let's sing - 鄺, 家邦 (良友門市部, 1974)
OCLC: 40507849
Keywords: Songbooks; Chinese

舉我所知. 聲韻音之零零碎碎 - 陳, 貞伯 (und, 1974)
private printing

實用英文文件 = Practical English writing - 馮立賢. (商務印書館, 1974)
OCLC: 22234025
Keywords: Affaires Formulaires; Blank forms; Business; Business Forms; Commercial correspondence; Letter writing

中文辭典 - 高宏文. (明光出版社, 1974)
OCLC: 23325712
Keywords: Chinese language; Chinese language Dictionaries; Chinois (Langue) Dictionnaires; Dictionaries; Dictionnaires; dictionaries

知音集 = Let's Sing - 鮑, 雲龍 (潮僑社, 1974)